2006
DOI: 10.1177/089686080602600613
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Management of Peritoneal Dialysis Patients Undergoing Hernia Surgery without the use of Interim Hemodialysis

Abstract: Objective To review the feasibility of undertaking elective hernia repair in peritoneal dialysis (PD) patients without converting them to hemodialysis. Design A 10-year retrospective review of prospectively collected data. Setting PD unit of a university-based hospital. Patients and Methods All patients received regular exchanges until the morning of the surgery and remained off dialysis for the first 48 hours postoperatively. After that, PD was gradually reintroduced. The patients on continuous ambulatory PD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 9 publications
3
33
0
2
Order By: Relevance
“…In fact, there have been several reports showing that APD had a lower rate of herniation than CAPD [41,44], although other reports have shown no significant difference in the incidence of herniation with APD versus CAPD [48] (Table 4). However, the latter reports compared dwell volumes of more than 2 L. Therefore, it may be useful to maintain only up to approximately 1 L to prevent an increase in abdominal pressure and to decrease the risk of peritoneal leakage and herniation in high-risk patients [49,50]. A Japanese report showed that intra-abdominal pressure was not significantly increased when dwell volume was less than 1 L in Japanese patients [51].…”
Section: Effects Associated With Peritoneal Leakage or Herniationmentioning
confidence: 99%
“…In fact, there have been several reports showing that APD had a lower rate of herniation than CAPD [41,44], although other reports have shown no significant difference in the incidence of herniation with APD versus CAPD [48] (Table 4). However, the latter reports compared dwell volumes of more than 2 L. Therefore, it may be useful to maintain only up to approximately 1 L to prevent an increase in abdominal pressure and to decrease the risk of peritoneal leakage and herniation in high-risk patients [49,50]. A Japanese report showed that intra-abdominal pressure was not significantly increased when dwell volume was less than 1 L in Japanese patients [51].…”
Section: Effects Associated With Peritoneal Leakage or Herniationmentioning
confidence: 99%
“…There is no consensus on whether it is necessary to convert to HD or on the time needed to resume CAPD after surgery [4,6,9,10,16,23]. One investigation revealed that some centers in the UK received temporary HD postoperatively and that the median duration of resuming CAPD was 4 weeks (1 day − 8 weeks)[23].…”
Section: Discussionmentioning
confidence: 99%
“…Continuous ambulatory peritoneal dialysis (CAPD) is a prevalent and acceptable alternative therapy for patients with end-stage renal failure (ESRL) and has many economic bene ts, is convenient, avoids the pain of establishing the vascular access needed for hemodialysis (HD) and provides a survival advantage while retaining residual renal function (RRF) [1][2][3]. Abdominal wall hernia is an unavoidable noninfectious complication in CAPD patients that is considered to be caused by the sustained increase in intra-abdominal pressure caused by injecting a large amount of dialysate during CAPD and by deterioration of abdominal wall tissue at this stage [4,5]. The main types of hernias in CAPD patients include inguinal, umbilical, incisional and epigastric, and the former two types are the most common [4,6].…”
Section: Introductionmentioning
confidence: 99%
“…Die PD kann mit niedrigeren Füllvolumen oder mittels Cyclertherapie (IPD) innerhalb von 72 Stunden postoperativ gestartet werden. Eine Überbrückung mittels Hämodialyse ist nicht erforderlich [8,9]. Bei einer intraperitonealen Netzapplikation erfolgt die Neoepithelialisierung nach 2 Wochen und ist nach einem Monat komplett ausgebildet [10].…”
Section: Hernien Und Pdunclassified